Chinese Herbal Medicine for Mild Cognitive Impairment: A Systematic Review and Meta‐Analysis of Cognitive Outcomes. (14th July 2016) - Dong, Lin; May, Brian H; Feng, Mei; Hyde, Anna J; Tan, Hsiewe Ying; Guo, Xinfeng; Zhang, Anthony Lin; Lu, Chuanjian; Xue, Charlie Changli
Abstract : Mild cognitive impairment (MCI) is a condition that may be prodromal to the development of dementia. There remain, as yet, no approved pharmaceutical interventions for MCI. Chinese herbal medicines (CHMs) have a long history of use for cognitive impairments and some plant ingredients have shown neuroprotective actions in experimental studies. This review assesses the current clinical evidence from controlled clinical trials for the effects of CHMs on cognitive outcomes as measured by Mini‐mental state examination (MMSE) or Alzheimer's Disease Assessment Scale‐Cognitive subscale (ADAS‐Cog). Fifty one studies (4026 participants) were included. These compared CHM with placebo, supportive care, pharmaceutical treatment or combined CHM with a pharmaceutical in an integrative setting. For the eight randomised controlled trials (RCTs) of comparisons with placebo, MMSE was significantly higher in the CHM groups (MD 1.56 [0.78, 2.34] I 2 = 85%, n = 503), similarly for eight RCTs of comparisons with supportive care (MD 1.77 [1.33, 2.21] I 2 = 0%, n = 555). Benefits were also evident in comparisons with some pharmaceuticals and with integrative treatment. The small size of most studies and methodological weaknesses mean that these results should be interpreted with caution. Further studies employing rigorous methods are required to investigate the potential benefits of these CHMs for MCI. Copyright © 2016 John Wiley & Sons, Ltd.